PHYSIOLOGICAL EFFECT OF YOGA ON DIFFERENT BODY SYSTEMS - Pratap Singh, *Bhanu; Dr, Deepa; Dadhich, Om Prakash (AYUSHDHARA, 2016)
The life style of men changed due to technological modernization and advancement of science. Increased standard of living has brought a great comfort to mankind but they are worried about health. Everyone is sick having either physical or mental problem. Yogasanas are one of the important parts of yogic exercises which contribute to physical as well as mental health. Yoga is a mind body practice that combines stretching exercises, controlled breathing and relaxation. It is considered a mind body type of complementary and alternative medicine practice. The health benefits of Yoga with a regular practice of Yoga poses, breathing exercise and meditation is grouped into three kinds: physiological, psychological and biochemical effects. Yogasanas have an equal balancing effect on all organs simultaneously without making an effort to think about different parts and internal organs of the body. Yogasanas have a combined effect on all the systems simultaneously. Chiefly Yogasanas cause positive effects on digestive system like Padmasana, Vajrasana, Gomukhasana etc. If we talk about respiratory system, a regular practice of deep Pranayama and Shavasana help to regulate inspiration and expiration. In endocrine system, Yogasanas regulate and control the secretion of hormones from all glands in the body. Regular practice of Yogasanas promotes purification and circulation of blood in different systems of the body. Likewise here are some physiological benefits of Yoga that can get through a regular Yoga practice.